2017
DOI: 10.1186/s12913-017-2476-9
|View full text |Cite
|
Sign up to set email alerts
|

From habits of attrition to modes of inclusion: enhancing the role of private practitioners in routine disease surveillance

Abstract: BackgroundPrivate practitioners are the preferred first point of care in a majority of low and middle-income countries and in this position, best placed for the surveillance of diseases. However their contribution to routine surveillance data is marginal. This systematic review aims to explore evidence with regards to the role, contribution, and involvement of private practitioners in routine disease data notification. We examined the factors that determine the inclusion of, and the participation thereof of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…Private health providers who cater to nearly 80% of ambulatory healthcare, do not contribute much to IDSP. 5,6 People seek health information either from curiosity generated by the media, by virtue of their own, or a family member's illness. Health information seeking, sometimes referred to as infodemiology has been suggested as another avenue of disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Private health providers who cater to nearly 80% of ambulatory healthcare, do not contribute much to IDSP. 5,6 People seek health information either from curiosity generated by the media, by virtue of their own, or a family member's illness. Health information seeking, sometimes referred to as infodemiology has been suggested as another avenue of disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally our findings emphasized the need for better intervention coherence. In line with Phalkey et al’s [19] recommendations, the involvement of PPs requires periodic training, supportive supervision, and regular feedback to improve PPs’ compliance with the mandatory TB notification policy. Uplekar [20] described five practical components required to facilitate a fully operational mandatory TB notification system to work optimally: policies and regulations, systems and reporting mechanisms, service provider orientation, feedback, and monitoring and evaluation.…”
Section: Discussionmentioning
confidence: 81%
“…Most policy changes in the area of payment systems are inadequately informed by research [ 21 ]. Besides this, several studies identified epidemiological knowledge of the practitioner as the most important determinant of notification [ 15 , 22 – 25 ]. No doubt, there is room for improvement in Hungary as well.…”
Section: Discussionmentioning
confidence: 99%